A Replication of the Internal Validity Structure of Three Major Teaching Rating Scales. (May 2017) - Peters, Scott J.; Pereira, Nielsen
Even as the importance of replication research has become more widely understood, the field of gifted education is almost completely devoid of replication studies. An area in which replication is a particular problem is in student identification research, since instrument validity is a necessary prerequisite for any sound psychometric decision. To begin to address this issue, our study sought to replicate the internal validity structure of three teacher rating instruments. The goal was to determine whether data gathered using these instruments fit their published internal validity structures. Results indicated all three instruments failed to meet traditional fit criteria, but to varying degrees, and that further replication or instrument revision are needed before these instruments can be used with confidence.